Nghiên cứu các yếu tố tác động đến quyết định đầu tư trực tiếp ra nước ngoài của Việt Nam: Trường hợp Campuchia - Võ Thanh Thu; Lê Quang Huy; Lê Thị Bích Diệp (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This article analyzes the key factors affecting foreign direct investment (FDI) of Vietnamese enterprises in Cambodia, one of the two biggest FDI markets of the country, using multivariate regression technique in addition to qualitative approaches. Two groups of factors under investigation include: (i) those promoting FDI activities; and (ii) factors attracting FDI capital. From the results obtained, the paper draws a few policy implications for attracting FDI to Cambodia and encouraging this kind of investment in other foreign country in general and in Cambodia in particular.